Implementation of PAI Learning In Building Religious Values For Students At Muhammadiyah 3 SMP School Bandung City - Joned Ceilendra Saksana (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The aim of this research is to analyze the implementation of PAI learning in an effort to build religious values at SMP Muhamadiyah 3 Bandung City. And to also analyze the PAI teacher's intracurricular learning curriculum regarding building religious values of the Muhammadiyah 3 Middle School school community in Bandung City. Research method with a qualitative analysis approach. Data collection techniques include field observation, in-depth interviews, and literacy studies. The result is the implementation of Islamic religious education in building religious values at SMP Muhammadiyah 3 Bandung City. It has been implemented effectively and efficiently. Applied in everyday life through the habit of greeting each other, ethics, good manners, noble character, respecting teachers, loving friends. Intracurricular activities are also carried out, such as early morning prayers, congregational noon prayers, coaching, religious lectures, memorizing Al-Quran letters. Providing an example for the school community. In building students' religious values, this is done centrally according to aspects and concepts.